Characterization of physicochemical and microbial quality, functional properties, and shelf stability of fermented tigernut-based probiotic beverages - Yeboah, Stephen; Ohemeng, Agartha; Donkor, Leticia; Saalia, F. K.; Annor, George Amponsah; Kunadu, Angela Parry-Hanson (Frontiers in Food Science and Technology, 2023)
Tigernuts and millet are indigenous underutilized crops in West Africa that have versatile applications in food processing. These crops are rich in fermentable carbohydrates, resistant starch, fiber, and micronutrients, making them ideal candidates for pre- and probiotic (synbiotic) foods. This study utilized whole tigernuts in a dairy–millet-based fermented beverage called brukina, turned it to a synbiotic, and assessed the functional and physicochemical profiles, microbial quality, and shelf stability of the beverage. The tigernut–millet agglomerate was prepared by incorporating cellulose-hydrolyzed tigernut fibrous (TNF) cake and non-hydrolyzed TNF (10% and 15%, respectively) into millet and allowing to ferment for 12 and 24 h. Brukina produced from composite tigernut milk: dairy in a ratio of 40%:60% was inoculated with the probiotic Lacticaseibacillus casei after pasteurization. The beverage was analyzed for physicochemical, proximate, and functional properties and microbiological stability at 5°C and 25°C. The obtained data were subjected to analysis of variance (ANOVA) in Minitab version 17 using a general linear model to determine the variability, interactions, and significance of the measured product characteristics. The agglomerate water absorption capacity (l/g) ranged from 0.70 ± 0.17 to 0.89 ± 0.17, bulk density (g/l) from 0.55 ± 0.04 to 0.63 ± 0.00, and swell index (%) from 1.62 ± 0.08 to 1.80 ± 0.06. The agglomerate prepared from dough and fermented for 12 h had excellent functional characteristics and was selected for synbiotic brukina production. Moisture content of the product decreased (p < 0.001) with tigernut incorporation ranging from 78.85% to 70.45%, while sodium, phosphorus, protein, total carbohydrate, and crude fiber increased with tigernut incorporation (p < 0.05). Synbiotic brukina supported the growth of L. casei attaining 11 log CFU/mL with a corresponding increase in lactic acid production and was microbiologically safe at 5°C and 25°C for 5 days compared to unpasteurized and uninoculated probiotic control (p < 0.05). The addition of whole tigernuts and L. casei to brukina enhanced its nutritional content with a shelf stability of 3 days.